2015
DOI: 10.1016/j.physbeh.2014.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Naproxen attenuates sensitization of depressive-like behavior and fever during maternal separation

Abstract: Early life stress can increase susceptibility for later development of depressive illness though a process thought to involve inflammatory mediators. Isolated guinea pig pups exhibit a passive, depressive-like behavioral response and fever that appear mediated by proinflammatory activity, and which sensitize with repeated separations. Treatment with an anti-inflammatory can attenuate the behavioral response during the initial separation and separation the following day. Here we used the cyclooxygenase inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…Experiential factors, such as social experiences, appear to be particularly important drivers of neuroimmune differences across a wide range of species. For instance, the presence of dominance hierarchies in pair-housed male rats is predictive of ambient IL-1 concentration in brain (Barnum et al , 2008); repeated social defeat in male mice altered chemokine-mediated recruitment of myeloid cells to the CNS (Wohleb et al , 2013); and maternal separation of guinea pig pups produced a constellation of sickness-like behaviors that are ameliorated by drugs with anti-inflammatory properties (Hennessy et al , 2015). Finally, the identification of specific developmental epochs during which individuals may be susceptible (vulnerable) to stress-, pain- or inflammation-dependent changes in later stress reactivity also emerged as key individual drivers of enhanced stress reactivity later in life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiential factors, such as social experiences, appear to be particularly important drivers of neuroimmune differences across a wide range of species. For instance, the presence of dominance hierarchies in pair-housed male rats is predictive of ambient IL-1 concentration in brain (Barnum et al , 2008); repeated social defeat in male mice altered chemokine-mediated recruitment of myeloid cells to the CNS (Wohleb et al , 2013); and maternal separation of guinea pig pups produced a constellation of sickness-like behaviors that are ameliorated by drugs with anti-inflammatory properties (Hennessy et al , 2015). Finally, the identification of specific developmental epochs during which individuals may be susceptible (vulnerable) to stress-, pain- or inflammation-dependent changes in later stress reactivity also emerged as key individual drivers of enhanced stress reactivity later in life.…”
Section: Discussionmentioning
confidence: 99%
“…Agents with more global anti-inflammatory properties, such as alpha-melanocyte stimulating hormone (α-MSH), have been shown to rescue stress-induced reductions in food intake and HPA axis aberrations (Milligan et al , 1998). IL-10, a potent anti-inflammatory cytokine, has also been shown to reverse sickness-like behavioral responses in a guinea pig model of maternal separation (Hennessy et al , 2011), and sensitization of febrile responses produced by this maternal separation experience was reversed with naproxen, a relatively selective inhibitor of cyclooxygenase-2 (COX-2) activity (i.e., the enzyme responsible for production of mature prostaglandin E2 synthesis)—a final common mediator of many inflammation-related effects (Hennessy et al , 2015). Although there is some recent evidence suggesting that antagonists to the P2X7 (purinergic) receptor can reverse some stress-related effects (presumably due to blocking IL-1 release), these effects are generally modest, perhaps because they are blocking only one cytokine within the context of many (Catanzaro et al , 2014, Lord et al , 2014).…”
Section: Neuroimmune Consequences Of Stress and Implications For Elabmentioning
confidence: 99%
“…For example, ibuprofen (another NSAID) was able to attenuate depressive-like behavior in ill tumor-bearing mice (Norden et al, 2015). Additionally, Hennessy and colleagues (Hennessy et al, 2015) reported that naproxen ameliorated social separation-induced depressive-like behavior in guinea pigs, with this pattern of separation-induced depressive-like behavior strikingly similar to sickness behavior exhibited during a state of illness (Hennessy et al, 2014), and which also involves a decline in social behavior (Henry et al, 2008). …”
Section: 0 Materials and Methodsmentioning
confidence: 99%
“…3 tested whether administration of naproxen, a non-steroidal anti-inflammatory drug (NSAID), would attenuate the aging-related decline in social interaction, with the idea that NSAID treatment might alleviated aging-related inflammation and temper any general achiness and/or malaise that could account for declines in social behavior during late aging in females. Naproxen—a non-selective cyclooxygenase (COX) inhibitor—was selected as an initial pharmacological approach because it has been classically used to reduce fever, pain, and inflammation (Clarke et al, 1994), and more recently to alleviate illness-related changes in social behavior in guinea pigs (Hennessy et al, 2015). Together, these experiments represent our development of a tractable working model to assess mechanisms underlying late-aging associated social deficits.…”
Section: 0 Introductionmentioning
confidence: 99%
“…Guinea pig pups exhibit a depressive-like hunched posture when exposed to a several-hour period of isolation in a novel environment, and this response sensitizes with repeated separation. Both the initial and sensitized response can be attenuated with administration of anti-inflammatory compounds (Hennessy et al, 2007, 2015; Perkeybile, Schiml-Webb, O’Brien, Deak, & Hennessy, 2009; Schiml-Webb, Deak, Greenlee, Maken, & Hennessy, 2006). Although evidence indicates that social separation and negative social interactions can readily incite inflammatory-mediated depressive reactions, the ability of affiliative social partners to buffer these responses has not been systematically investigated.…”
Section: Introductionmentioning
confidence: 99%